Differential inhibitory effects of endocannabinoids on neuronal firing of mouse meningeal afferents - Georgii Krivoshein; Adriana Della Pietra; Juha Savinainen; Arn M. J. M. van den Maagdenberg; Rashid Giniatullin (The Journal of Headache and Pain)
Abstract Background Increasing endocannabinoids (endoCBs), anandamide (AEA) and 2-arachidonoylglycerol (2-AG), through inhibition of the degrading hydrolase enzymes, fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL), respectively, has been proposed as approach to alleviate migraine pain. Notwithstanding, the impact of AEA and 2-AG on neuronal firing of meningeal afferents, which is relevant to the genesis of migraine pain, remains elusive. Methods The impact of AEA and 2-AG on meningeal nerve afferent firing was examined through electrophysiological evaluation upon application of 50 mM KCl with or without DMSO, exogenous AEA (10 µM), or 2-AG (10 µM) to separate groups of C57BL/6J mouse hemiskull preparations. At the end of each experiment, capsaicin (1 µM), an agonist of TRPV1 channels, was tested, as a positive control of presumably nociceptive firing. Advanced clustering and spectral analysis on the electrophysiological data allowed differentiating spiking patterns with respect to their temporal and neurochemical profiles. Activity-based protein profiling and liquid chromatography with tandem mass spectrometry was used to assess endogenous FAAH and MAGL activity and determine endogenous levels of AEA and 2-AG in mouse meninges. Results Local application of endoCBs decreased KCl-induced firing of meningeal nerve afferents, which was most profound for AEA. AEA first produced a short, mild activation in firing, which was followed by a long-lasting reduction. Instead, 2-AG directly led to a short-lasting reduction in firing. Cluster analysis revealed that the transient activation by AEA involved fibers with small-amplitude spikes fired at rates of 1–2 Hz, whereas the persistently suppressed fibers consisted of high-amplitude spikes fired at rates exceeding 10 Hz. Only AEA inhibited subsequent capsaicininduced firing in the afferents long after AEA application, suggesting a broader mode of action for AEA than 2-AG. The more profound inhibitory effects of AEA are consistent with the observed higher activity of FAAH over MAGL and lower level of endogenous AEA than 2-AG in mouse meninges. Conclusion Our study revealed a stronger anti-nociceptive action of AEA than of 2-AG, as measured by meningeal afferent firing in mouse hemiskulls. This difference can be exploited for relieving migraine pain by primarily increasing the tone of AEA through inhibition of FAAH outside the central nervous system.